2017
DOI: 10.1101/241372
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Converting a broad matrix metalloproteinase family inhibitor into a specific inhibitor of MMP-9 and MMP-14

Abstract: MMP-14 and MMP-9 are two well established cancer targets for which no specific clinically relevant inhibitor is available. Using a powerful combination of computational design and yeast surface display technology, we engineered such an inhibitor starting from a non-specific MMP inhibitor, N-TIMP2. The engineered purified N-TIMP2 variants showed enhanced specificity towards MMP-14 and MMP-9 relative to a panel of off-target MMPs. MMP-specific N-TIMP2 sequence signatures were obtained that could be understood fr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…The naturally occurring inhibitor TIMP‐2 has provided the starting point for the design of other selective MMP inhibitors. Using yeast surface display technology, fluorescently labelled catalytic domains of MMP‐14 and MMP‐9 can be used to identify mutant TIMP‐2 that has greater specificity for either one MMP or the other . The mutant TIMP‐2 molecules inhibit the catalytic function of MMP‐14 and MMP‐2 in vitro , and reduce cell migration in a breast cancer cell line .…”
Section: Recent Advances In the Development Of Mmp Inhibitorsmentioning
confidence: 99%
“…The naturally occurring inhibitor TIMP‐2 has provided the starting point for the design of other selective MMP inhibitors. Using yeast surface display technology, fluorescently labelled catalytic domains of MMP‐14 and MMP‐9 can be used to identify mutant TIMP‐2 that has greater specificity for either one MMP or the other . The mutant TIMP‐2 molecules inhibit the catalytic function of MMP‐14 and MMP‐2 in vitro , and reduce cell migration in a breast cancer cell line .…”
Section: Recent Advances In the Development Of Mmp Inhibitorsmentioning
confidence: 99%
“…Here, the greater challenge becomes evolving selectivity among MMPs, since native TIMPs broadly inhibit most MMPs. Earlier studies employed the isolated N-terminal domain of TIMP-2 (N-TIMP-2) as a scaffold for engineering selective inhibitors of MMP-14 and MMP-9 (17,18). In addition to the core inhibitory epitope that binds in the enzyme active site, this domain includes the TIMP AB-loop, which contacts the MMP catalytic domain at a nonconserved surface exosite, giving opportunities for evolution of specificity.…”
Section: Discussionmentioning
confidence: 99%
“…Prior work has focused primarily on engineering the N-terminal domain of TIMPs, an independently folding and stable domain that retains MMP inhibitory capability (15,16). Yeast surface display of N-TIMP-2 was used successfully as a directed evolution platform to develop inhibitors of MMP-9 and MMP-14 with enhanced affinity and selectivity (17)(18)(19)(20). Recently, we demonstrated that full-length TIMPs could offer further advantages as scaffolds for engineering inhibitors with improved binding toward target MMPs.…”
Section: Introductionmentioning
confidence: 99%
“…We and others have engineered N-TIMP2 with the goal of converting it into a highly specific inhibitor of one MMP type (28)(29)(30)(31)(32). Our group first explored how various single mutants in N-TIMP2 affect its affinity and specificity to various MMPs (29).…”
Section: Introductionmentioning
confidence: 99%